Variasi genetik pertumbuhan pada uji provenans dan uji keturunan Eusideroxylon zwageri di Bondowoso, Jawa Timur - Mudji Susanto (Jurnal Pemuliaan Tanaman Hutan, 2010)
A Provenance test for ex-situ conservation and a progeny test of Eusideroxylon Zwageri was established in 2006 and 2008 at Sumberwringin, Bndowoso, East java. The trials were evaluated every year to examine genetic and environment effects on growth. There significant differences among provenances for height both at the provenance and progeny test. The differences among families within provenance was statistically significant for height and diameter. Estimated individual heritabilities at one year old for height and diameter. Estimated individual heritabilities at one year old for height and diameter r=were hight (hi2 = 0.58 for height and hi2 = 0,52 for diameter).